Wacław Makowski — teoretyk i praktyk polskiego autorytaryzmu, bohater dwóch poświęconych mu monografii - Zmierczak, Maria (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The article is an extensive discussion and comparison of books published by two authors in 2014, Grzegorz Ławnikowicz and Władysław T. Kulesza, devoted to the same figure from the inter-war period, Wacław Makowski. They present the political ideas of Makowski, a theorist of the state, who created a concept of social state, a state based on the solidarity principle, and, at the same time, was an opponent of liberal democracy based on the protection of human rights. Apart from bringing Makowski back from obscurity, the present author shows first of all how different two books on the same topic can be, a difference stemming from the research methodology applied, but probably also from the personality of the two authors. A rhetorical question remains whether the fact that two scholars explore the same topic for quite a while reflects well on communication between research centres in Poland.
Keywords: autorytaryzm; II Rzeczpospolita; konstytucja; demokracja; reżim sanacyjny